Modulation of feedback-related negativity during trial-and-error exploration and encoding of behavioral shifts. - Sallet, J; Camille, N; Procyk, E (2013)
The feedback-related negativity (FRN) is a mid-frontal event-related potential (ERP) recorded in various cognitive tasks and associated with the onset of sensory feedback signaling decision outcome. Some properties of the FRN are still debated, notably its sensitivity to positive and negative reward prediction error (RPE)-i.e., the discrepancy between the expectation and the actual occurrence of a particular feedback,-and its role in triggering the post-feedback adjustment. In the present study we tested whether the FRN is modulated by both positive and negative RPE. We also tested whether an instruction cue indicating the need for behavioral adjustment elicited the FRN. We asked 12 human subjects to perform a problem-solving task where they had to search by trial and error which of five visual targets, presented on a screen, was associated with a correct feedback. After exploration and discovery of the correct target, subjects could repeat their correct choice until the onset of a visual signal to change (SC) indicative of a new search. Analyses showed that the FRN was modulated by both negative and positive prediction error (RPE). Finally, we found that the SC elicited an FRN-like potential on the frontal midline electrodes that was not modulated by the probability of that event. Collectively, these results suggest the FRN may reflect a mechanism that evaluates any event (outcome, instruction cue) signaling the need to engage adaptive actions.